Design and characterization of a plastic scintillation detector system for Beta tagging - Li, Xin (2019)
The aim of this work is to test the detection performance of the PVT-based plastic scintillation detector system for detection of 𝛽 particles in future recoil-𝛽 tagging studies at JYFL. Characterization of the detector was performed with 𝛼, 𝛽, and 𝛾 radiations using silicon photomultiplier as the photodetector of the scintillation light. Characteristics of the detector were analysed using a data acquisition system and an analysis programme. The detection efficiency was extracted from the measured geometrical, absolute, and intrinsic efficiencies. Effect of external reflector was tested to give the light collection an enhancement by a factor of ~ 3. With a thin layer of ZnS(Ag) covering the frontal face of the scintillator, pulse shape discrimination properties were studied. Signals produced by 𝛼 particles and 𝛾 rays were efficiently separated by means of the slow scintillation property of ZnS(Ag) in response to hadrons and 𝛼 particles. The timing properties in slow and fast signal reconstructions were extracted by analysis of the pulse shapes. In order to stop 𝛽 particles having energies up to 10MeV within the scintillator, the scintillator array was planned to have eight frontal pieces with dimensions of 128×6×10 mm3 in horizontal direction and thirteen pieces with dimensions of 48×24×10 mm3, in vertical direction. The aim is to replace the planar Ge detector used previously in correlation techniques with the position sensitive DSSD. This will improve the overall detection efficiency of 𝛽 particles and 𝛾 rays at the MARA focal plane. A simulation of the correlation techniques used in recoil-beta tagging was carried out by using cosmic muons. Coincidence events were effectively identified with the relation between electron range and energy deposited in the scintillator. A research training report was included in Chapter 6 of this thesis. A systematic attempt was made aiming at exploring a method for evaluation and optimization of the photon detection efficiency associated with light guide geometry. The angular response of the SiPM to incident light was examined with my design of an optical pulse generator. A series of optical analyses was performed to extract the angular distribution of the light output emerging from different types of light guide geometries. Based on these experimental and analytical results, a mathematical formalism was developed as a practical method for evaluation and optimization of photon detection efficiency in applications of light guide coupled to a photodetector more than qualitatively.